Improving Students' Critical Thinking Skills with The Discovery Learning Model Assisted by Realia Learning Media - Ardita, Made Widya; Agustika, Gusti Ngurah Sastra; Wiyasa, I Komang Ngurah (Universitas Pendidikan Ganesha, 2023)
Science learning emphasizes the provision of understanding, experience and direct practice to develop students' potential. But the facts on the ground show that the learning conditions in schools have not gone well. This study aims to determine the effect of the Discovery Learning model assisted by realia media on the critical thinking skills of science content in fifth grade elementary school students. This study was a quasi-experimental design using the Nonequivalent Control Group Design. The population in this study were 190 students with two sample groups, namely the experimental group which consisted of 38 students and the control group which consisted of 37 students. Methods of data collection using a test form of description. The research data were analyzed using descriptive statistical analysis techniques and inferential statistical analysis techniques using the t-test. The results of the analysis of the hypothesis showed that tcount was 3.407 and ttable was 1.993 with a significant level of 5% and dk = 73. Because tcount 3.407 was greater than ttable 1.993, Ha was accepted that there are differences in students' critical thinking skills in science content who are taught with the Discovery Learning model assisted by realia media and the group of students who are not taught with the Discovery Learning model assisted by realia media in fifth grade elementary school students.